Remoção de biodiesel com óxido de ferro magnético - Santos, Kenia Gabriela dos (2020)
Magnetic nanoparticles are used for water treatment and the highlight is the magnetic iron oxide. Thus, the first experiment, on a laboratory scale, was conducted with the purpose of studying the behavior of the iron oxide adsorbent (Fe3O4) with diesel adsorbates with 8% biodiesel (B8) and pure biodiesel (B100). The adsorption capacity was analyzed using techniques such as Fourier Transform Infrared Spectroscopy (FTIR) and Thermogravimetric Analysis (TGA). With this study, it is concluded that iron oxide has a greater tendency to adsorb biodiesel. With that, the second research was carried out, using magnetic iron oxide with cassava leaf charcoal (CFM) to adsorb biodiesel in water. The factorial 22 Central Rotational Composite Design was employed, with 3 central and 4 axial points. An aqueous medium was utilized, intending to simulate the spillage of biodiesel in water. The pH of the water/biodiesel mixture was changed with concentrations of hydrochloric acid, and with different concentrations of CFM incorporated into the iron oxide. It was possible to identify that the best condition for the adsorption of biodiesel was when there was a higher proportion of iron oxide, verified by thermogravimetric, fluorescence, and turbidity analyzes. Thus, the magnetic adsorbent of the present work proved to be valid for the removal of biodiesel in water.